(untitled) (The Pakistan Development Review, 2012)
Traditionally, developed countries are the major exporters of services; however, technological developments in IT and communications over the last two decades have made it possible for developing countries to exploit their comparative advantage in some modern services. The driving force for this comparative advantage is the large pool of semi-skilled and skilled graduates in emerging countries who can deliver their services across borders, using advanced communication technologies. Why do emerging countries have increasing modern services exports? How are these exports explained by theory? What are the factors behind this export growth and the reasons to expect future growth? These are some of the important questions that researchers and policy-makers would like to find answers to and an attempt has been made to answer these questions in this paper. Identification of the sources of services export growth from emerging and developing countries can be attempted through established theories of goods trade and production. This paper reviews selected theory and empirical work in order to explain the underlying causes for growing exports of services. Causes for the export of modern services may include a comparative advantage of the exporting country, cost reduction for the importing firm through outsourcing, reduction in trading costs due to technological improvements and an increase in gains from services trade.